Направления капитализации электроэнергетических компаний Украины в условиях институциональных изменений - Завгородняя, О.П. (Стратегія і механізми регулювання промислового розвитку, 2013)
На основе анализа базовых условий функционирования отечественной электроэнергетики, действующей модели энергорынка выявлены факторы капитализации генерирующих компаний. Обосновано влияние институциональных факторов на эффективность функционирования генерирующих компаний. Показано, что основными характеристиками институциональной структуры, создающей стимулы к повышению эффективности деятельности предприятий энергетического сектора, являются утверждение приоритетов энергоэффективности и инновационности. Определены направления повышения капитализации электроэнергетических компаний с учетом институциональных изменений. На основі аналізу базових умов функціонування вітчизняної електроенергетики, діючої моделі енергоринку виявлено чинники капіталізації генеруючих компаній. Обґрунтовано вплив інституціональних чинників на ефективність функціонування генеруючих компаній. Доведено, що основними характеристиками інституціональної структури, яка створює стимули до підвищення ефективності функціонування підпри ємств енергетичного сектору, є затвердження пріоритетів енергоефективності та інноваційноті. Визначено напрями підвищення капіталізації електроенергетичних компаній з урахуванням інституціональних змін. The paper proves that a reliable and balanced supply of users with energy requires further reformation of the Ukrainian electric energy complex, market of electric power on the basis of progressive competition model of two-sided contracts, development and capitalization of generating companies by means of providing and strengthening the reproduction-innovative process. It is set that the basic conditions for increasing the efficiency of functioning of generating companies are: the liquidation of government monopoly on a wholesale of electric power; transition to the direct market of contract mutual relations between the subjects of market of electric power; liquidation of the cross subsidizing of users of electric power; establishment of transparent, economically grounded tariffs on a production, transmission and supplying to electric power; corporate strategic planning on the basis of power balances. The influence of external and internal institutional factors (institutional structure) on the efficiency of activity of enterprises of power sector is well-grounded. It is established that basic characteristics of the institutional structure that creates incentives to increase the efficiency of functioning of energy enterprises are the approvement of priorities of energy efficiency and innovation. The ways of increasing the capitalization of energy companies are identified. The important conditions for attracting the investment resources in the electric power industry are: representativeness, authenticity, availability of the information about the activity of power companies for all levels of management, possible investors and wide circles of public; transparency and availability for the users of the mechanism of establishment of tariffs for electric power. The participation of electricity users in power rates setting is possible through the creation of the Council of users.